Influence of basalt fiber on mode I and II fracture properties of asphalt mixture at medium and low temperatures. (April 2021) - Guo, Qinglin; Chen, Zhipeng; Liu, Pengfei; Li, Yiming; Hu, Junxing; Gao, Ying; Li, Xiaoxu
Highlights: Effect of basalt fiber on mixed mode fracture of asphalt mixture was investigated. Asymmetric semi-circular bend test was carried out. Critical stress intensity factor and fracture energy were determined. GMTS criterion is suitable for the prediction of fracture initiation angle. Linear empirical fracture criterion has good applicability to asphalt mixture. Abstract: Basalt fiber could effectively improve the crack resistance of asphalt mixture. However, most cracks in asphalt pavement present complex fracture characteristics. Effect of basalt fiber on the mixed mode fracture resistance of asphalt mixture is still unknown. Thus, the asymmetric semi-circular bend test was used to study the mode I and II fracture properties of the control and basalt fiber reinforced asphalt mixtures (BFRAM) at low and medium temperatures. Influences of basalt fiber on the critical stress intensity factor and critical fracture energy of asphalt mixture were investigated. The applicability of different fracture criterions to asphalt mixture also was discussed. Results indicate that the critical stress intensity factors of BFRAM first decreases and then increases with the rise of M e (which describes different fracture modes) at medium and low temperatures. Basalt fiber soundly improves the critical fracture energy of asphalt mixture at medium and low temperature even though it reduces the critical stress intensity factor at 20 ℃. The reinforcing effect of basalt fiber is optimal for the mixed mode fracture. Generalized maximum tangential stress (GMTS) criterion is suitable for the prediction of fracture initiation angle. The linear empirical fracture criterion has good applicability to the control and basalt fiber reinforced asphalt mixtures. This work can be used to analyze the mixed modes fracture of asphalt layers.